Behavioral Drivers of Tax Compliance Among Smes: The Impact of Tax Morale, Perceived Fairness, and Trust in Government - Ndahani Ngwasa (dialektika kontemporer, 2026)
This research investigated the impact of tax morale, perceived fairness, and trust in government on tax compliance among Small and Medium Enterprises (SMEs) in Ilala District, Dar es Salaam, Tanzania, with a specific focus on the Kariakoo commercial area. Based on the Slippery-Slope Framework (SSF), which looks at how trust and power affect how taxpayers act, the study used a quantitative research design. Structured questionnaires were used to get information from owners and managers of small and medium-sized businesses. Before analysis, the data were checked for linearity, normality, multicollinearity, and homoscedasticity to make sure that the assumptions of multiple regression were met. Multiple regression analysis was conducted to examine the strength, direction, and significance of the relationships between the behavioral drivers and tax compliance. The findings revealed that perceived fairness, tax morale, and trust in government all exert positive and significant effects on tax compliance, with perceived fairness identified as the most robust predictor. The overall model exhibited significant explanatory power, underscoring the essential influence of behavioral factors in promoting voluntary compliance among SMEs. These results confirm the SSF by demonstrating that sustainable tax compliance is influenced not only by enforcement mechanisms but also by psychological and ethical factors, such as fairness, trust, and moral obligation. The study enhances comprehension of SME tax behavior within a Tanzanian context, highlighting the significance of incorporating behavioral insights into tax compliance strategies. Keywords: tax morale; perceived fairness; trust in government; tax compliance